PRELIMINARY PHARMACOGNOSTIC AND PHYSICO-CHEMICAL EVALUATION OF ROOT AND LEAVES OF PATHA (CYCLEA PELTATA (LAM.) HOOK.F. & THOMS) - Nair, *Sunitha.S.; Hameed, A. Shahul (International Journal of Ayurveda and Pharma Research, 2018)
The quality control of herbal crude drugs and their bio constituents is of paramount importance in justifying their acceptability. The crude drugs can be identified systematically on the basis of their morphological, histological, chemical, physical and biological studies. Cyclea peltata (Lam) Hook. f. Thoms belonging to the family Menispermaceae is a common plant seen in South India. It is mentioned in Ayurvedic classics by the name Rajapatha and is one of the important drugs used in Ayurveda therapeutics and is used widely in different formulations in medical practice. The aim of the study is to evaluate the preliminary pharmacognostical and phytochemical characters of Cyclea peltata (Lam) Hook. f. Thoms. Pharmacognostical evaluation of the plant Cyclea peltata (Lam) Hook. f. Thoms. was done by studying the macroscopic and microscopic features of leaf and root of the plant. The physical parameters studied included foreign matter, moisture content, volatile oil, total ash, acid insoluble ash, water soluble extractive, alcohol soluble extractive, fibre content and sugar content. The preliminary phytochemical analysis included qualitative chemical analysis, Thin Layer Chromatography, High Performance Thin Layer Chromatography and Atomic Absorption Spectroscopy. Various pharmacognostic and preliminary phytochemical characters observed in this may help in standardization, identification and carrying out further research in Cyclea peltata (Lam) Hook. f. Thoms.